Ellagic acid inhibits melanoma growth in vitro - James Daniel Jensen; Jeffrey H. Dunn; Yuchun Luo; Weimin Liu; Mayumi Fujita; Robert P. Dellavalle (PAGEPress Publications, 2011)
Ellagic is a polyphenolic compound with anti-fibrotic and antioxidant properties as well as exhibits antitumor properties against various cancer cells in vitro. There are few studies, however, which examine the effects of ellagic acid on melanoma. In the present study, we observe effects of ellagic acid on melanoma cells in vitro. Three metastatic melanoma cell lines (1205Lu, WM852c and A375) were examined to determine the effects of ellagic acid on melanoma cell viability, cell-cycle, apoptosis, NF-κβ activity, and IL-1β & IL-8 secretion. Cell viability assays demonstrated that ellagic acid possesses an inhibitory effect on cell proliferation at concentrations between 25 and 100 µM. In addition, ellagic acid promoted G1 cell cycle arrest, increased levels of apoptosis and decreased synthesis of IL-1β and IL-8 in melanoma cells. Ellagic acid also decreased NF-κβ activity, suggesting at least one potential mechanism by which ellagic acid may exert its effects in melanoma cells. Our findings support further investigation into prospective roles for ellagic acid as a therapeutic, adjuvant, or preventive agent for melanoma.